Chemo- and regioselective reductive deoxygenation of 1-en-4-yn-ols into 1, 4-enynes through FeF3 and TfOH co-catalysis. Issue 35 (7th April 2016) - Yang, Zonglian; Kumar, Rapolu Kiran; Liao, Peiqiu; Liu, Zhaohong; Li, Xingqi; Bi, Xihe
Abstract : We report chemo- and regioselective direct reductive deoxygenation of 1-en-4-yn-3-ols into 1, 4-enynes through FeF3 and TfOH cooperative catalysis under NBSH-mediated conditions. Abstract : We report chemo- and regioselective direct reductive deoxygenation of 1-en-4-yn-3-ols into 1, 4-enynes through FeF3 and TfOH cooperative catalysis under NBSH-mediated conditions. Further, we show the efficient synthesis of a pharmaceutically significant 1, 4-enyne. The present methodology can also be used for chemo- and regioselective direct deoxygenation of other alcohols.